Business operation model with sharia concerns and proposed resolution for Takaful - Ahmad Razimi, Mohd Shahril; Romle, Abd Rahim; Ahmad, Aziemah (IDOSI, 2017)
Islamic insurance or known as Takaful has been widely used in the world especially Islamic countries because of the awareness of implementing shariah principles in their business transactions. Takaful operators have implemented a few types of Takaful business operation model which believed to be based on shariah principles. However, there are some issues regarding the permissibility of the models by shariah scholars. Hence, this paper aims to analyse the basic principles of Takaful and eventually an analysis of available Takaful models that being used in the industry. In addition, a proposed model will be discussed as the resolution of all of the models available.